Cockfight in the cotton: a moral crusade in microcosm - Hawley, F. Frederick (Contemporary crises, 1989)
Due to its unique socio-cultural heritage, Louisiana is one of only four states in which cockfighting is legal. During the 1980s various animal-rights advocacy groups have attempted to stigmatize and criminalize the activity. This situation has precipitated local and state-wide conflicts in which urban-cosmopolitan "progressive" New South boosters, allied with traditional and non-conventional animal-rights activists, are pitted against congeries of rural, blue collar "sports-men" who are, in turn, allied with state and national lobbying organizations of their own. Participant-observation, archival research, content analysis and life histories are used in the exploration of a clash of cultures, or more specifically, a clash of world-views. Not surprisingly, the present lobbying activity and proposed legislation contain many of the attributes of the prototypical moral crusade. In addition, the milieux of both cockfighters and reformers are described and contrasted.